Fiscal dimensions of EMU. - MASSON, Paul R. (1996)
Considers three issues relating to fiscal policy and EMU: the appropriateness of the debt and deficit preconditions; the need for fiscal discipline and policy coordination; the case for a supranational fiscal authority. Argues that (1) on the first issue, the conditions are not in themselves necessarily flawed, but difficulties arise as a result of the measures taken to meet them; (2) the need to ensure an appropriate policy mix inevitably creates a need for fiscal coordination, which naturally leads in to the question of supranational control. Concludes that fiscal federalism, with its implications for redistribution, has more to do with politics than economics.